El silencio administrativo: su ineficacia en la región de educación la libertad - Torres Vásquez, Alejandro (2011)
Presently work the causes have been investigated that it determines that the administrative silence becomes in ineffective for the educational ones he/she gives secondary education he/she gives the Region he/she gives Education he/she gives The Freedom in the years 2007 and 2008. The procedure for the selection gives the sample it i the compound number tombola, because he/she gives the total he/she gives 2,800 professors, he/she decided to make the study in 20%, equivalent at 560 educational, then you proceeded to select the elements muéstrales in each Educational Institution he/she gives the counties he/she gives Ascope, Bolivar, Great Chimú, Julcán, Pacasmayo, Sánchez Carrión and Trujillo, until already reaching the percentage mentioned. Also, the analytic method - synthetic it was good to interpret the results and to obtain the summations, it could be that educational he/she gives secondary education he/she gives the Region he/she gives Education he/she gives The Freedom they lack he/she gives training regarding the law he/she gives the administrative and very few silence they make uses he/she gives artificial this it figures in the Units he/she Local gives Educational Administration and in Central the Organism he/she gives the Region he/she gives Education he/she gives The Freedom. You arrives, after processing the results he/she gives the work, to demonstrate that artificial the figures gives the administrative silence it i ineffective for the professors he/she gives the studied regional environment, due to the lack he/she gives information, at the distance he/she gives (you organs give the administration and to the slowness in the attention gives the procedures.